Pushdown Processes: Games and Model Checking - Walukiewicz, Igor (BRICS Report Series, 1996)
Games given by transition graphs of pushdown processes are considered. It is shown that if there is a winning strategy in such a game then there is a winning strategy that is realized by a pushdown process. This fact turns out to be connected with the model checking problem for the pushdown automata and the propositional mu-calculus. It is shown that this model checking problem is DEXPTIME-complete.